Neighboring faiths a Christian introduction to world religions - Corduan, Winfried (Downers Grove, IL : IVP Academic, 2012)
For students seeking to understand what other religions believe and practice, and for small groups and churches who want to become more effective in reaching those from other cultures and religions, Neighboring Faiths is an indispensable guide.
Religion: study and practice -- Judaism -- Islam: basics and issues -- Islam: understanding 9/11 and radical islam -- Baha'i -- Zoroastrianism -- Traditional religions: introduction and African religion -- Native American religion -- Hinduism -- Buddhism -- Jainism -- Sikhism -- Chinese popular religion -- Shinto and Japanese religions.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Religions; Christianity and other religions; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books